METHODOLOGY OF PROFESSIONAL APPROACH IN ENGLISH LANGUAGE TEACHING FOR MEDICAL STUDENTS - Buranova, Dilafruz (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The training of medical specialists with English language knowledge in higher education of Uzbekistan requires the implementation of a number of tasks, such as improving the methods of learning the language and effective measures for organizing activities in this direction. It is important for medical students to master language skills in the field of their profession. In connection with the reduction of fundamental subjects at medical universities in Uzbekistan, teaching methods of teaching foreign languages should be reviewed, especially in recent years, as the modernization of higher medical education creates the problem of a sharp reduction in humanities, including foreign languages. For significantly shortened hours, it is necessary to introduce effective teaching methods of English for medical students. There is a need to create integrative models of language teaching in the medical profession (ESP). This study shows that creating a special professional environment for language learning has its advantages while teaching English as a discipline. The methodology of integration into the specialty and the relationship between the subjects allows students to learn the educational material in the most convenient and interesting way for them.
Keywords: English language; methodology; medical; students; ESP; specialty; education; profession